2018
DOI: 10.1080/09540121.2018.1465176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of participation in a randomised controlled trial of an integrated palliative care intervention on HIV-associated stigma

Abstract: We conducted in Kenya a mixed-methods randomised controlled trial (RCT) of a nurse-led palliative care intervention integrated with anti-retroviral therapy (ART) provision for the management of HIV. Here we report qualitative findings showing increased resistance to HIV-associated stigma among trial participants. A mixed method design was chosen to enable identification of the active ingredients of the intervention and exploration of participants' experiences of receiving the intervention. The RCT was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…good quality of life for people living with HIV (Lazarus et al, 2016), then careful assessment of pain and symptoms must be a priority. This requires the replication of simple interventions to deliver person-centred HIV outpatient care (Logie and Harding, 2005b, Lowther et al, 2018a, Lowther et al, 2018b, Lowther et al, 2016, Lowther et al, 2015a), strategies to ensure pain relieving drugs are available in pharmacies and are prescribed (Logie and Harding, 2005a), and that low cost, effective interventions such as pain self-management for people living with HIV are delivered (Nkhoma et al, 2018, Nkhoma et al, 2015. Importantly, our data highlight the important of self-reported outcomes from diagnosis until the end of life.…”
Section: Resultsmentioning
confidence: 90%
“…good quality of life for people living with HIV (Lazarus et al, 2016), then careful assessment of pain and symptoms must be a priority. This requires the replication of simple interventions to deliver person-centred HIV outpatient care (Logie and Harding, 2005b, Lowther et al, 2018a, Lowther et al, 2018b, Lowther et al, 2016, Lowther et al, 2015a), strategies to ensure pain relieving drugs are available in pharmacies and are prescribed (Logie and Harding, 2005a), and that low cost, effective interventions such as pain self-management for people living with HIV are delivered (Nkhoma et al, 2018, Nkhoma et al, 2015. Importantly, our data highlight the important of self-reported outcomes from diagnosis until the end of life.…”
Section: Resultsmentioning
confidence: 90%
“…69 One study that examined a patient-centred holistic care intervention among adults living with HIV in Kenya found that simple mechanisms for support, compassion and improved communication in routine care increased self-esteem, stigma resilience and increased confidence to disclose HIV status. 58…”
Section: Qualitative or Mixed-methods Approachesmentioning
confidence: 99%
“…The majority of the included papers described interventions that targeted specific groups living with HIV such as women, 47,53,64,67 children/families, 49,56,60,70,71 ethnic subgroups 51,53,67 or key populations such as adolescents 49,56 and MSM, 46,68 while only two included people living with HIV with other comorbidities, i.e. chronic pain 58 or mental health issues. 54 Some interventions were multi-level, including community members, social networks, family members/caregivers and healthcare workers.…”
Section: Types Of Hiv-related Stigma Interventions Target Groups and Settingsmentioning
confidence: 99%
“…Integrated care counters this through therapeutic impartiality, empathy through compassionate care, social support, and appreciative and non-judgmental communication [ 105 ]. Moreover, integrated care aims to promote health literacy with PLWH’s ability to use health services on their own and build resilience and self-efficacy to cope with the complex situation [ 29 , 106 ].…”
Section: Discussionmentioning
confidence: 99%